IMPROVING READING AND ENGLISH SPEAKING SKILLS THROUGH THE “SAY SOMETHING” STRATEGY - Hariati, Puji; Supriyani, Epi (VISION, 2023)
All abilities in English cannot be separated from one another. Integrating one ability with another is necessary to avoid weakening one side of the ability. Based on several studies, the ability to read and speak English has a very large relationship in teaching and learning English. By reading, students can add vocabulary as a very important thing in speaking English. One of the most important things in the science of vocabulary is to make it easier to speak. Authentic reading texts can be explained directly in speaking to help students' abilities. Students can understand authentic reading texts in various ways. One way is to directly say something about what they have read.